THE OPTIMALIZATION OF EXTRACTION METHOD OF AVOCADO LEAVES - Herayati, Herayati; Fitri Nadiyah, Syakirah (Indonesian Journal of Cosmetics, 2025)
This study aims to determine the most effective extraction method to obtain bioactive compounds from avocado (Persea americana Mill.) leaves, which are known for their antioxidant and antibacterial activities. Four extraction methods were evaluated—maceration, digestion, Soxhlet extraction, and ultrasonic extraction—using methanol and water as solvents. Evaluation was based on yield and stock solution concentration. Results showed that ultrasonic extraction produced the highest yield with a stock concentration of 2.5% m/v, indicating superior extraction efficiency compared to the other methods. Maceration and Soxhlet extraction produced moderate values, while digestion produced the lowest stock solution concentration (0.9%). These findings indicate that ultrasonic extraction is a rapid and efficient technique for extracting bioactive compounds from natural materials, making it highly relevant for application in cosmetic and pharmaceutical product development.